\(ω\) - Fuzzy Translation and Multiplication in BH-Algebras - Prasanna, A.; Premkumar, M.; Mohideen, S. Ismail (Technological Innovation in Engineering Research Vol. 3, 2022)
This paper focuses on the novel exploration of \(ω\) - Fuzzy Translation and Multiplication in \(B H-\) Algebras. To explore this \(ω\)-Fuzzy is defined first in \(B H\) - Algebras and used in Fuzzy Translation and Multiplication in \(B H-\) Algebras by tracing its algebraic properties.